THE EFFECT OF JOB CHARACTERISTICS, EMPLOYEE EMPOWERMENT AND COMPENSATION ON PERFORMANCE ON CUSTOMER SERVICES OF BANK MANDIRI JEMBER BRANCH - Susanti, Indah; Firdaus, Muhammad; Indah Handayani, Yuniorita (MBA : Journal of Management and Business Aplication, 2021)
This study aims to determine the effect of job characteristics, employee empowerment and compensation on employee performance at Bank Mandiri Jember Branch. The population in this study were all employees of PT. Bank Mandiri Tbk totaling 162 people. The sample in this study amounted to 41 respondents. The sampling technique used in this study is a non-probability sampling technique, namely the Accidental Sampling approach. The data analysis method used is multiple linear regression analysis. The results of this study indicate that the variables of job characteristics, employee empowerment and compensation have a simultaneous effect on employee performance at Bank Mandiri Jember Branch. Partially, these results also show that the variables of employee empowerment and compensation have a significant effect on employee performance. While the variable of job characteristics has no significant effect on the performance of employees of Bank Mandiri Jember Branch. Keywords: Job Characteristics, Employee Empowerment, Compensation, Performance